Effect of maxillary osteotomy on speech in cleft lip and palate: perceptual outcomes of velopharyngeal function. Issue 6 (14th August 2013) - Pereira, Valerie J.; Sell, Debbie; Tuomainen, Jyrki
Abstract: Background: Abnormal facial growth is a well‐known sequelae of cleft lip and palate (CLP) resulting in maxillary retrusion and a class III malocclusion. In 10–50% of cases, surgical correction involving advancement of the maxilla typically by osteotomy methods is required and normally undertaken in adolescence when facial growth is complete. Current evidence for the impact of the surgery on velopharyngeal function is weak and mixed. Aims: The first objective of the study was to investigate the nature of the effect of maxillary osteotomy on the perceptual outcomes of velopharyngeal function in CLP. The second objective was to establish if speech changes seen early at 3 months post‐operation persisted for a year after/following surgery', when it is considered that the maxilla is relatively stable. Methods & Procedures: Twenty consecutive patients with CLP undergoing maxillary osteotomy by a single surgeon were seen pre‐operatively (T1), 3 months (T2) and 12 months (T3) post‐operation. A non‐cleft control group (NonCLP) undergoing surgery was also recruited. Speech data were collected using the Cleft Audit Protocol for Speech—Augmented (CAPS‐A). A velopharyngeal composite score‐summary (VPC‐SUM) was derived from specific CAPS‐A‐rated parameters. An external CAPS‐A‐trained therapist, blinded to the study, rated the randomized samples and inter‐rater reliability was established. Outcomes & Results: For the CLP group, hypernasality and nasal turbulence increased significantly post‐operation. Planned comparisons were significant for T1–T2 only with a medium effect size. For hypernasality, the CLP group differed statistically from the NonCLP group at T2 and T3. For nasal turbulence, the CLP group differed statistically from the NonCLP group at T2. For VPC‐SUM, there were statistically significant changes post‐operatively between T1–T2 and T1–T3 only with medium effect sizes for the CLP group only. Conclusions & Implications: This study provides evidence that maxillary osteotomy affects patients with and without CLP differently. In patients with CLP, surgery may impact negatively on velopharyngeal function for speech and changes seen early on at 3 months post‐operatively appear to persist at 12 months postoperatively. The findings in this study have implications for the speech care pathway of patients with CLP undergoing maxillary osteotomy in terms of assessment, review and management.